151 Sodium and Chlorine Requirement of Yellow-feathered Broilers Aged from 1. (7th December 2018) - Jiang, S; Yu, H; Gou, Z; Li, L; Wang, Y; Jiang, Z; Lin, X
Abstract: The experiment was conducted to investigate the effects of dietary Na+ and Cl- level on growth performance, excreta moisture, blood biochemical variables, and carcass traits in broilers, and to estimate the optimal dietary sodium and chlorine level for yellow-feathered broilers fed a corn-soybean meal diet. A total of 2850 1d, 22d, and 43d male broilers were randomly assigned to one of five dietary treatments. Each treatment consisted of six replicates with 40 birds per replicate in the trail of 1–21 days of age or 30 birds per replicate in the trail of 22–42 days of age or 25 birds per replicate in the trail of 43–63 days of age. Dietary treatments included the basal diet (control, and without additional Na+ and Cl-) and the basal diet supplemented with NaCl and NaHCO3 (the ratio of Na+ and Cl- is 1:1 in dietary, and the dietary Na+ and Cl- levels are 0.1%, 0.2%, 0.3%, and 0.4%). Feed and water were provided ad libitum. Results showed that dietary supplemental Na+ and Cl- significantly improved the growth performance, and daily water consumption of broilers (P<0.05), decreased mortality (P<0.05); BWG observed a quadratic broken-line effect of increasing with dietary Na+ and Cl- addition (R 2 = 0.966, P = 0.009 from 1 to 21 days, R 2 = 0.9785, P < 0.0001 from 22 to 42 days, R 2 = 0.9752, P = 0.0002 from 43 to 63 days). Na+ and Cl- supplementation significantly increased OSM in serum (P<0.05); significantly reduced levels of uric acid, glucose, triglyceride, and total cholesterol (P<0.05). Na+ and Cl- addition significantly increased thigh muscle percentage (P<0.05). Base on growth performance, the optimal dietary Na+ and Cl- level estimated by NLIN were 0.14%, 0.10%, and 0.09% for yellow-feathered broilers aged from 1 to 21 days, 22 to 42 days, 43 to 63 days, respectively.